MEDIA DIGITAL SEBAGAI AGORA BARU PEWARTAAN GEREJA DALAM SEMANGAT KNOW, SHARE, MEET, EXPRESS YOUCAT - Dessindi, Kristhalia (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2020)
The development of digital technology poses a challenge for the Church to find new ways to spread the faith to Generation Z. The media is a good supporter to facilitate the Church in proclaiming her teachings. In the era of the industrial revolution 4.0, digital media became one of the means of proclamation that the Church and pastoral activists could use to spread faith to Generation Z. The author's exploration of generation Z led the author to be interested in the theme